2020
DOI: 10.3389/fpls.2020.591715
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Oxidase Induces Systemic Resistance in Sugar Beet Against Cyst Nematode Heterodera schachtii

Abstract: Ascorbate oxidase (AO) is an enzyme involved in catalyzing the oxidation of apoplastic ascorbic acid (AA) to dehydroascorbic acid (DHA). In this research, the potential of AO spraying to induce systemic resistance was demonstrated in the interaction between sugar beet root and cyst nematode Heterodera schachtii and the mechanism was elucidated. Plant bioassays showed that roots of AO-sprayed plants were infested by a significantly lower number of females and cysts when compared with mock-sprayed control plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…Contrarily, AO overexpression triggered the accumulation of basal ROS, which had a protective role in rice antiviral defense . In addition, exogenous spraying of AO strongly enhanced plant nematode resistance in sugar beet . It seems that AO functions in totally contradictory ways on defense against abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, AO overexpression triggered the accumulation of basal ROS, which had a protective role in rice antiviral defense . In addition, exogenous spraying of AO strongly enhanced plant nematode resistance in sugar beet . It seems that AO functions in totally contradictory ways on defense against abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, exogenous spraying of AO strongly enhanced plant nematode resistance in sugar beet. 66 It seems that AO functions in totally contradictory ways on defense against abiotic and biotic stresses. Accordingly, AO is supposed to be a mysterious enzyme, whose various roles need further exploration.…”
mentioning
confidence: 99%
“…Induced resistance against nematodes seems generally correlated with activation of the phenylpropanoid pathway. For example in Singh et al (2019Singh et al ( , 2020a, systemic activation of the phenylpropanoid pathway in response to application of COS-OGA in rice or AO in sugar beet was observed to be correlated with induced resistance to parasitic root-knot and cyst nematodes. Similarly, Huang et al (2016) showed that thiamine-induced resistance against M. graminicola in rice involved lignin deposition in plant roots, and this correlated with enhanced transcription of OsPAL1 and OsC4H, two genes involved in the phenylpropanoid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the functional annotation of DEGs in sweet potato (Lee et al, 2021) and in cotton (Kumar et al, 2019) demonstrated "response to salicylic acid" as the key enriched BP against nematode infestation. The role of JA, as another plant signaling compound, has been investigated upon nematode infection in different plant species (Hamamouch et al, 2011;Fan et al, 2015;Regis, 2015;Singh et al, 2020). JA-mediated tolerance against RKN infection is reported through alteration in the photosynthetic and antioxidative defense mechanisms in tomato plants (Bali et al, 2018).…”
Section: Discussionmentioning
confidence: 99%